(STUDI POPULASI ORANGUTAN SUMATERA (PONGO ABELII) DI KAWASAN STASIUN PENELITIAN KETAMBE TAMAN NASIONAL GUNUNG LEUSER ACEH TENGGARA - Dodi Syahputra; Ruskhanidar; Zakiah (LPPM STIK Pante Kulu, 2022)
The Ketambe Research Station is an important habitat for the Sumatran orangutan (Pongo abelli), which experiences many disturbances from the community, such as forest encroachment and illegal logging. This condition has caused 7% habitat destruction. The impact of habitat destruction has led to a decline in the orangutan population. This study aims to determine the population of Sumatran orangutans at the Ketambe research station. The study took place at the Ketambe research station, Mount Leuser National Park (TNGL) Aceh Tenggara, for three months from April to June 2021, using the purposive sampling method, and the orangutan population data collection technique using the line transect method as many as 9 (nine) transects. , placed: riverbanks, plains, ridges, and mountain peaks. Data analysis for this study used the formula d = N / 2 w L: Estimating nest density (d), number of nests (N), length of observation path (L), width of observation path (w), according to (Van Schaik, 1995) is Estimated density of each nest/species found. The observation paths are 1 km long each and the left and right are 25 m wide, the Sumatran orangutan population density found is 0.7291 Individuals/Km², with a total of 104 nests. From the total area of ​​observation 45 ha (450,000m²). Based on the results of the study, the most preferred type of meranti (hopea cernua) was the Sumatran orangutan for making nests at the ketambe research station. The most distribution of nests based on diameter size is 21-40 cm, based on nest height is at a height of 10-20 m, based on nest position is in position 1, based on nest class is in class C, and based on tree height is in class 15-25 m. Based on the results obtained, the types of trees that orangutans prefer for nesting can be used as a type of planting activity, orangutan habitat restoration.